Behaviour and fate of trace metal element in seawater: an overview - Dzulkafli, Noor Fazreen; Noor Azmi, Azran Azhim; Musa, Md Noor (2014)
External and internal factors from the environment and ecosystem significantly affect the seawater system’s chemical balance especially the trace metal elements. The chemical balances changes of trace metals species will gives adverse impact to marine ecosystem and biodiversity. As far as concern, the quantitative relationship between trace metals and ecology is difficult to establish, as the process is too complex and difficult to be understand. Therefore, physical and chemical models have been used to predict the evolution and complexity of trace metal with ecosystems and environmental variability of the seawater. The bioavailability study model is important to monitor the bioaccumulation of trace metals in marine organism. This review paper addresses the basic concepts of global concentration and distribution of trace metal in seawater and its bioavailability towards marine organism. Moreover, some chemical models of trace metal elements for both; surface water and deep sea water and it relationship with the ecological cycles in seawater are discussed. The combination of physical, chemical and bioavailability model will provide a better understanding of the behavior, distribution and fate of trace metals elements in seawater.